Effects of a Rugby League Match Simulation on Decision-Making in Elite Junior Rugby League. Issue 7 (July 2021) - Redman, Kellyanne; Steel, Kylie; Kelly, Vincent; Siegler, Jason
Abstract : Abstract: Redman, K, Steel, K, Kelly, V, and Siegler, J. Effects of a rugby league match simulation on decision-making in elite junior rugby league. J Strength Cond Res 35(7): 1972–1980, 2021—The paucity of research on decision-making in Rugby league within the context of a match, and the potential for age and playing experience to influence decision-making ability, warrants further investigation. Therefore, the aim of this study was to determine the effects of a simulated rugby league match on decision-making in elite junior rugby league players. Twenty male junior rugby league players (age 15.9 ± 0.9 years, body mass 87.3 ± 14.3 kg, height 1.82 ± 0.07 m, playing experience 10.2 ± 2.4 years) completed a match simulation protocol that replicated the physiological demands of an elite junior rugby league match. Decision-making performance was measured prematch, midmatch, and postmatch simulation through a reactive agility test and video-based temporal occlusion task. Upper- and lower-body neuromuscular measures as well as ratings of perceived exertion were obtained before decision-making assessments to quantify fatigue. A 2-way mixed analysis of variance with Bonferroni corrections was used to assess changes during the simulation, and significance was accepted at p < 0.05. The main finding of this study was despite observing a decline in neuromuscular function during the match simulation protocol (countermovement jump declined 1.9 ± 0.6 cm [95% confidence intervals 0.4–3.5]; p < 0.05), this decline did not significantly affect decision-making performance (reactive agility test [ p = 0.58]; temporal occlusion [ p = 0.88]). These results suggest elite junior rugby league players are capable of sustaining performance during a progressively fatiguing match simulation.